How social capital enables or restricts the livelihoods of poor peri-urban farmers in Mexico. Issue 3 (3rd April 2017) - Méndez-Lemus, Yadira; Vieyra, Antonio
ABSTRACT: Poor farmers in peri-urban territories are subjected to the gradual transmutation of their livelihoods while they try to escape from poverty and adapt to an increasingly urban environment. Social capital seems to influence the outcomes of such livelihoods, and might expand chances and choices to improve poverty status, but also to follow their own paths. This article explores the mechanisms through which this capital enables or restricts such livelihoods in two peripheral municipalities in Mexico. The findings highlight the importance of informal institutional and non-institutional mechanisms in regulating access to, and distribution of, resources in peri-urban territories.